Personality Traits, Self-Esteem and Menstrual Cycle as Correlates of Consumer Impulsiveness and Regret - Vujović, Tanja M.; Ranđelović, Dušan J.; Tripković, Anđelka V. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper examines consumer impulsiveness and post-purchase dissonance among female students as well as their relationship with personality traits, self-esteem and menstrual cycle. The study involved 253 female students pursuing Bachelor’s, Master’s and PhD degrees at the Faculty of Economics, Faculty of Medicine, Faculty of Law, Faculty of Philosophy, Faculty of Technical Sciences and Faculty of Arts of the University of Priština in Kosovska Mitrovica. The instruments used in the study were the impulsiveness scale, the consumer regret scale, and the self-esteem scale. The analysis indicated that these are highly reliable instruments whose items can be regarded as homogeneous and representative. The results obtained show that consumer impulsiveness among the female students is at an average level, whereas the post-purchase regret is at a lower level compared to the theoretical average. In addition, a positive correlation was found between consumer impulsiveness and neuroticism, while self-esteem has a negative correlation with consumer impulsiveness and is its significant predictor. On the other hand, there is a negative relationship between post-purchase regret and cooperativeness, conscientiousness, openness to experience, and self-esteem. Conscientiousness and self-esteem can also be identified as predictors of post-purchase regret among female students, with self-esteem having a greater independent contribution.